2017
DOI: 10.1186/s12014-017-9146-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies of the proteomes of circulating microparticles: key roles for galectin-3-binding protein-expressing microparticles in vascular diseases and systemic lupus erythematosus

Abstract: Subcellular microvesicles (MVs) have attracted increasing interest during the past decades. While initially considered as inert cellular debris, several important roles for MVs in physiological homeostasis, cancer, cardiovascular, and autoimmune diseases have been uncovered. Although still poorly understood, MVs are involved in trafficking of information from cell-to-cell, and are implicated in the regulation of immunity, thrombosis, and coagulation. Different subtypes of extracellular MVs exist. This review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Nervous system diseases multiple sclerosis EAE in Gal-3-deficient mice reduction in severity of EAE [83] multiple sclerosis spinal cord in EAE Gal-3 observed at early stage before symptoms [84] Huntington's disease mouse model of Huntington's disease plasma and brain Gal3 levels correlated with disease severity [40] brain ischemia time course analysis of Gal-3 in hippocampus usefulness of early stage of Gal-3 for ischemic brain [39] brain ischemia temperature-dependent enhancement of Gal-3 hypothermic prevention of Gal-3 [30] cerebral infarction cerebral artery occlusion up-regulated Gal-3 in late stage of permanent ischemia [85] Renal disease renal ischemia Gal-3 deficient mice less acute renal tubular necrosis [86] renal fibrosis unilateral ureteral obstruction renal fibroblast activation by macrophage-secreted Gal-3 [87] renal ischemia unilateral ureteral obstruction Gal-3 protect renal tubules [88] lipid-induced renal injury Gal-3 deficient mice more marked in Gal-3 deficient mice [89] Liver disease NAFLD/NASH Gal-3 deficient mice attenuated inflammation and fibrosis [90] Connective tissue diseases SLE anti-Gal-3 antibody injected into skin induction of lupus-like histologic changes [73] Neoplasms glioma analysis of preneoplastic lesions expressed in preneoplastic lesions [43] ovarian cancer ovarian cancer xenografted mice.…”
Section: Animal Models Experimental Methods Experimental Findings Refsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nervous system diseases multiple sclerosis EAE in Gal-3-deficient mice reduction in severity of EAE [83] multiple sclerosis spinal cord in EAE Gal-3 observed at early stage before symptoms [84] Huntington's disease mouse model of Huntington's disease plasma and brain Gal3 levels correlated with disease severity [40] brain ischemia time course analysis of Gal-3 in hippocampus usefulness of early stage of Gal-3 for ischemic brain [39] brain ischemia temperature-dependent enhancement of Gal-3 hypothermic prevention of Gal-3 [30] cerebral infarction cerebral artery occlusion up-regulated Gal-3 in late stage of permanent ischemia [85] Renal disease renal ischemia Gal-3 deficient mice less acute renal tubular necrosis [86] renal fibrosis unilateral ureteral obstruction renal fibroblast activation by macrophage-secreted Gal-3 [87] renal ischemia unilateral ureteral obstruction Gal-3 protect renal tubules [88] lipid-induced renal injury Gal-3 deficient mice more marked in Gal-3 deficient mice [89] Liver disease NAFLD/NASH Gal-3 deficient mice attenuated inflammation and fibrosis [90] Connective tissue diseases SLE anti-Gal-3 antibody injected into skin induction of lupus-like histologic changes [73] Neoplasms glioma analysis of preneoplastic lesions expressed in preneoplastic lesions [43] ovarian cancer ovarian cancer xenografted mice.…”
Section: Animal Models Experimental Methods Experimental Findings Refsmentioning
confidence: 99%
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…90 K has been found in serum microparticles 18 , in nanoparticles 5 and exomeres 6 released by tumor cells. To investigate the structure of 90 K in the CSF we used a combined approach of ultrafiltration (3 kDa cut-off membrane) with SEC using commercial qEVsingle columns.…”
Section: Discussionmentioning
confidence: 99%
“…90 K has been detected in biological fluids such as blood 1,13,14 , milk 15 , and more recent studies also reported its presence in the CSF 16,17 . In the serum 90 K was found in circulating microparticles, where it was increased for systemic lupus erythematosus and venous thromboembolism patients 18 . 90 K expression was induced in viral infection 1 and deregulation was also found in some cancer types 13,19 .…”
mentioning
confidence: 99%
“…Microparticles have been previously described as originating from innate immune cells, such as neutrophils and monocytes, but microparticles derived from platelets are normally among the most numerous in the circulation and are considered important in inflammatory diseases. 1 In patients with metastatic gastric cancer, the level of circulating platelet microparticles is elevated 2 and platelet microparticles also play a role in metastasis of other cancers. It has been reported that platelet-derived lysophosphatidic acid, which is a potent bioactive phospholipid, supports and stimulates metastatic breast cancer cells.…”
mentioning
confidence: 99%